If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m(5m + 6) = -9 Reorder the terms: 5m(6 + 5m) = -9 (6 * 5m + 5m * 5m) = -9 (30m + 25m2) = -9 Solving 30m + 25m2 = -9 Solving for variable 'm'. Reorder the terms: 9 + 30m + 25m2 = -9 + 9 Combine like terms: -9 + 9 = 0 9 + 30m + 25m2 = 0 Factor a trinomial. (3 + 5m)(3 + 5m) = 0Subproblem 1
Set the factor '(3 + 5m)' equal to zero and attempt to solve: Simplifying 3 + 5m = 0 Solving 3 + 5m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5m = 0 + -3 5m = 0 + -3 Combine like terms: 0 + -3 = -3 5m = -3 Divide each side by '5'. m = -0.6 Simplifying m = -0.6Subproblem 2
Set the factor '(3 + 5m)' equal to zero and attempt to solve: Simplifying 3 + 5m = 0 Solving 3 + 5m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5m = 0 + -3 5m = 0 + -3 Combine like terms: 0 + -3 = -3 5m = -3 Divide each side by '5'. m = -0.6 Simplifying m = -0.6Solution
m = {-0.6, -0.6}
| 6(m+10)= | | [(54/6)-3]•2= | | (u^2-7u-2)+(5u^2-6u+4)= | | 3x+5=12.2 | | 7y=-13-4x | | -4y=-3-7x | | D=8/3(m-92) | | -2[5-(2+1)]-4=2(3-z) | | 8/3(m-92) | | 2x^2+4x=35 | | (6y^4)^5/(2y^3) | | 3-2x=x-15 | | 6/7y-11=-5 | | 3x-12x-9=0 | | 5+20xX=Y | | Y=1.8x+14.4 | | 2y=2+3x | | 8x-8=9x-2+7x | | 4+9x=6x-9 | | -9=2/3t | | Z-4=7 | | 11x+5(x-2)=10 | | -3(3n-4)=66 | | (r^8t^4-4)(r^8t^4-4)= | | 1/5x-6=2 | | 62=5(2a+4)+4a | | -a+3a=-6 | | 8=7y+3 | | (8x+7h)(8x+7h)= | | -2a-3a=-5 | | 6k+5k=-11 | | 6-4x=78 |